Metabolic changes in fibroblast-like synoviocytes in rheumatoid arthritis: state of the art review - Hu, Zhipeng; Li, Yuan; Zhang, Lili; Jiang, Yayi; Long, Caiyi; Yang, Qiyue; Yang, Maoyi (Frontiers in Immunology, 2024)
Fibroblast-like synoviocytes (FLS) are important components of the synovial membrane. They can contribute to joint damage through crosstalk with inflammatory cells and direct actions on tissue damage pathways in rheumatoid arthritis (RA). Recent evidence suggests that, compared with FLS in normal synovial tissue, FLS in RA synovial tissue exhibits significant differences in metabolism. Recent metabolomic studies have demonstrated that metabolic changes, including those in glucose, lipid, and amino acid metabolism, exist before synovitis onset. These changes may be a result of increased biosynthesis and energy requirements during the early phases of the disease. Activated T cells and some cytokines contribute to the conversion of FLS into cells with metabolic abnormalities and pro-inflammatory phenotypes. This conversion may be one of the potential mechanisms behind altered FLS metabolism. Targeting metabolism can inhibit FLS proliferation, providing relief to patients with RA. In this review, we aimed to summarize the evidence of metabolic changes in FLS in RA, analyze the mechanisms of these metabolic alterations, and assess their effect on RA phenotype. Finally, we aimed to summarize the advances and challenges faced in targeting FLS metabolism as a promising therapeutic strategy for RA in the future.